2015
DOI: 10.1016/j.nuclphysb.2015.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Solving the sign problems of the massless lattice Schwinger model with a dual formulation

Abstract: We derive an exact representation of the massless Schwinger model on the lattice in terms of dual variables which are configurations of loops, dimers and plaquette occupation numbers. When expressed with the dual variables the partition sum has only real and positive terms also when a chemical potential or a topological term are added -situations where the conventional representation has a complex action problem. The dual representation allows for Monte Carlo simulations without restrictions on the values of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 27 publications
(22 reference statements)
1
79
0
Order By: Relevance
“…This additional constraint makes the system much more stiff in a Monte Carlo simulation and the insertion of additional winding loops, i.e., additional charges is rare. This has, e.g., been observed in the simulation [29][30][31] of the worldline form [32] of the massless Schwinger model. It was found that in the grand canonical worldline simulation in particular the particle number suffers from very long autocorrelation times.…”
Section: Canonical Worldline Simulationssupporting
confidence: 56%
See 1 more Smart Citation
“…This additional constraint makes the system much more stiff in a Monte Carlo simulation and the insertion of additional winding loops, i.e., additional charges is rare. This has, e.g., been observed in the simulation [29][30][31] of the worldline form [32] of the massless Schwinger model. It was found that in the grand canonical worldline simulation in particular the particle number suffers from very long autocorrelation times.…”
Section: Canonical Worldline Simulationssupporting
confidence: 56%
“…A canonical worldline simulation as we have described here overcomes this problem, since the net-winding number of the fermion loops and thus the particle number is kept fixed. First tests with simulations of the worldline form [32] have shown that with the canonical worldline approach autocorrelation problems are much milder.…”
Section: Canonical Worldline Simulationsmentioning
confidence: 99%
“…Before we end this section, we would like to comment on the connection between our proof for the absence of the sign problem here and the one given in Ref. [29] for the massless Schwinger model. As shown in the previous work, the presence of gauge fields allows us to absorb the staggered fermion phase factors into the gauge fields.…”
Section: World Line Representationmentioning
confidence: 69%
“…For fermions in a worldline representation obtained from Grassmann integration, the Pauli principle requires that each site of the lattice is occupied exactly once with a fermionic element, i.e., a monomer, a dimer or a fermion loop (see, e.g., [6]). When increasing the chemical potential temporally winding loops start to dominate.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In this paper we will compare the results from canonical and grand canonical simulations. Before we discuss the canonical approach in the worldline representation, we briefly comment on the numerical simulation of the grand canonical ensemble described by (3) - (6). For a more detailed discussion see [4].…”
Section: The Model and Its Worldline Representationmentioning
confidence: 99%